Comparison of Infant Complication between Emergency and Caesarean Sections: A Meta-Analysis - Padlilah, Rahmi; Yulianti, Ika (Journal of Maternal and Child Health, 2020)
Background:  The World Health Organization (WHO) calls for all regions in the world not to have a caesarean section (SC) rate of more than 15%. Globally, since 2003-2018, Emergency Caesarean Section (EmCS) and Elective Caesarean Section (ElCS) actions have continued to increase by 4% each year to 21%. Previous studies report that EmCS increases the risk of complications in the fetus compared to ElCS. Based on the problem above, this study aims to analyze and compare complications experienced by the fetus in the process of Emergency Caesarean Section (EmCS) and Elective Caesarean Section (ElCS).Subjects and Method: This was systematic review and meta-analysis study, which was conducted from July-August 2019. The data were obtained from PubMed, Science Direct, Web of Science, Springer Link, and Cochrane Database. The keywords were "elective cesarean section (ElCS) AND emergency cesarean section (EmCS)" AND "emergency cesarean section (EmCS) and fetal complication" AND "elective cesarean section (ECS) and fetal complication" AND "elective cesarean section (EmCS) AND fetal complication" (ElCS) AND emergency cesarean section (EmCS) AND fetal complication.Results: Emergency cesarean section increases the likelihood of neonatal death 4 times higher than the elective cesarean section and is statistically significant (RR= 4.02; 95% CI= 2.41 to 6.72). Emergency cesarean section can increase the likelihood of apgar score decrease 2 times higher than elective cesarean section and statistically significant (RR= 2.07; 95% CI= 1.03 to 4.15). Emergency cesarean section is 1.62 times higher than elective cesarean section and statistically significant (OR= 1.62; 95% CI= 1.19 to 2.20).Conclusion: Emergency cesarean section can increase the likelihood of death, decrease Apgar score <6, and hypoxia in the fetus compared to elective cesarean section.Keywords: emergency cesarean section, elective cesarean section, meta-analysisCorrespondence: Ika Yulianti. Faculty of Health Science, Universitas Borneo Tarakan, North Kalimantan, Indonesia. Email: ikatamaevan@gmail.com. Mobile: +628115440036Journal of Maternal and Child Health (2020), 5(2): 200-205https://doi.org/10.26911/thejmch.2020.05.02.10